Characteristics and treatment patterns in patients with multiple myeloma in Japan: A retrospective cohort analysis. - Shinsuke Iida; Yusuke Yasutomi; Yevgeniy Samyshkin; Yi-Chen Chen; Chi-Chang Chen; Wen Shi Lee; Seok-Won Kim; Catherine McGuiness; Zifan Zhou; Simon McNamara (PLoS ONE)
Background Approval of proteasome inhibitors, immunomodulatory drugs, and anti-CD38 monoclonal antibodies (mAbs), such as daratumumab, has reshaped treatment patterns in patients with multiple myeloma (MM) in Japan. This retrospective study evaluated patient characteristics, treatment patterns, and trends in MM patients using Medical Data Vision, the largest electronic health records database in Japan with anonymous inpatient and outpatient health information. Methods Patients aged ≥18 years, with ≥2 records of an MM diagnostic and disease code and ≥1 record of MM treatment between 01 April 2008 and 30 June 2023 were included. Patients starting first-line (1L) treatment on or after 01 January 2020 were categorized into the 1+L cohort; those starting second-line (2L) treatment on or after 01 January 2018 were allocated to the 2+L cohort. Results Within the study period, 21,066 patients had an MM diagnosis, including 6,337 and 5,964 patients in the 1+L and 2+L cohorts, respectively. Median age was 74 years in both cohorts and gender distribution was similar (52.4% and 51.3% males, respectively). In the 1+L cohort, most patients (5,754/6,337; 90.8%) did not receive transplant, among whom 51.0% received 1L lenalidomide-based therapy, primarily daratumumab/lenalidomide/dexamethasone (DRd; 15.0%) or lenalidomide/dexamethasone (Rd;14.0%). In non-transplant patients, 1L DRd use increased from 6.0% in January-June 2020 to 28.0% in January-June 2023. In the 2+L cohort, 2L lenalidomide-based therapy use decreased from 65.0% in January-June 2018 to 37.0% in January-June 2023; daratumumab-based therapy increased from 14.0% to 39.0%. Retreatment with lenalidomide-, daratumumab-, and isatuximab-based therapy occurred in 44.1%, 35.2%, and 5.6% of patients, respectively. Conclusion The high use of lenalidomide and DRd in 1L, and high rates of retreatment with lenalidomide and anti-CD38 mAbs in 2L+ indicate a substantial need for new treatment modalities that can be used in 2L+ patients who previously received lenalidomide with/without an anti-CD38 mAb therapy.